Application of the herbicide combination tritosulfuron and florasulam by unmanned aerial vehicle in the winter wheat - Bošković, Biljana (Acta herbologica, 2023)
Wheat is one of the most important agricultural crops in the world used in human nutrition. Depending on the level of weediness, weedy plants can lead to significant yield losses, which according to some estimates are up to 10% worldwide. Unmanned aerial vehicles (UAVs) are widely used in chemical crop protection, but so far the effectiveness of herbicides applied by UAVs has not been sufficiently studied. The aim of this work was to investigate the possibility of using an UAVs for the application of the herbicide combination tritosulfuron and florasulam in the protection of wheat from weeds. The effectiveness of the mentioned combination of herbicides was tested in the case of application of a low volume of treating by UAV, as well as by means of a field sprayer. Combination of herbicides tritosulfuron and florasulam applied by UAV (volume rate 30 l ha-1) showed high efficiency in controlling the weed species Capsella bursa-pastoris, Lactuca serriola, Sinapis arvensis and Viola arvensis while the efficiency of the same combination was lower in the case of application with a field sprayer. Based on the results of the experiment, which indicated the good effectiveness of the herbicide, we can conclude that from the aspect of successful protection of wheat from weeds, the use of UAV is fully justified.